THE DEFINITION OF DEATH: PAST, PRESENT & FUTURE (Journal of Forensic Medicine & Toxicology, 2018)
In the past, death has often been defined as the separation of the soul and body. Human death definition was much easier in the past. When the heart and the lungs stopped working the person died. With advances in medical technology the distinction between life and deathhas become blurred. Life support technologies introduced in the 20th century have generated a new kind of patient, one whose brain does not function but whose heart and lungs continue to work. Life and death are not binary states, from one to the other there is a gradual transition. Cells die individually and the rhythm of life slows steadily to a halt. ‘Traditional formulation’ of death has been defined as thecomplete and irreversible cessationof the vital fluid flow ie.air and blood. ‘Whole brain formulation’ of death is defined as the irreversible loss of an organism’s ability to function as a whole. ‘Higher brain formulation’ of death is defined as the total and irreversible loss of consciousness and cognition. ‘Social death’, the socially dead are those bodies lacking personhood The definition of death continues to evolve with adoption of modern technology the future definition will be at Gene /DNA level.
Keywords: Definition of death; Traditional formulation of death; Whole brain formulation; Higher brain formulation Higher brain formulation; Social death